The Effect of Product Quality and Price on Customer Satis-faction of The Originote Skincare Products - Putri Sofi Awalia; Dwi Asri Siti Ambarwati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The reserchaims to examine the impact of product quality and price on customer satisfaction with The Originote skincare products. The research is motivated by the growing public awareness of skincare and the increasing interest in local skincare brands, particularly The Originote. The data is a questionnaire using a quantitative approach with a descriptive method. This research uses multiple linear regression analysis was employed to assess the variables. The findings reveal that product quality has a positive significant effect on customer satisfaction, where significance probability value of 0.000, which is less than 0.05. Consumers tend to prefer high-quality products as they offer a sense of security, comfort, and benefits that meet ex-pectations. However, price does not significantly, with a significance probability value of 0.534, which is greater than 0.05. This indicates that consumers prioritize product quality and ingredients over price. The study's implications highlight the need for companies to focus on maintaining and improving product quality to ensure and enhance customer satisfaction.